2010
DOI: 10.1177/0743558410361371
|View full text |Cite
|
Sign up to set email alerts
|

Redeeming Immigrant Parents: How Korean American Emerging Adults Reinterpret Their Childhood

Abstract: Korean American youth experience immigration-related parent-child challenges including language barriers, parent-child conflicts, and generational cultural divides. Using grounded theory methods, this article examines the ways in which 18 Korean American college-enrolled emerging adults retrospectively made sense out of their experiences of immigrant family hardships. Of those who narrated childhood hardship, over half narrated positive change in which they reinterpreted their relationship to their parents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 33 publications
3
54
0
1
Order By: Relevance
“…Overall, parenting practices that the emerging adults hoped to avoid with their own children are consistent with previous studies of immigrant emerging adults who identified similar areas of conflict or challenge (Kang et al, 2010;Qin, 2008). Our findings further revealed that the participants as emerging adults could now reflect on and discuss the context of their parents' practices and strategies selected during their adolescence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, parenting practices that the emerging adults hoped to avoid with their own children are consistent with previous studies of immigrant emerging adults who identified similar areas of conflict or challenge (Kang et al, 2010;Qin, 2008). Our findings further revealed that the participants as emerging adults could now reflect on and discuss the context of their parents' practices and strategies selected during their adolescence.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, considering emerging adult children's perceptions of past parenting is one important way to reveal how parent socialization is a bidirectional process. Children actively participate in this dynamic process, in part by reflecting on, interpreting, and making sense of experiences with their own parents (Kang et al, 2010). Similar to Lamborn's studies (Lamborn & Moua, 2008;Lamborn et al, 2013), Hmong American emerging adults were both critical and accepting of different aspects of their parents' parenting, suggesting that there was some continuity in the values and practices that they wanted to pass on to their own children, and some discontinuity.…”
Section: Discussionmentioning
confidence: 80%
“…There is some evidence, however, that acculturation-based conflict in adolescence, similar to everyday conflict, may not have negative long-term consequences—at least for some families. A qualitative study of Korean American college students, for instance, found that a majority reported acculturation-related conflicts with parents during adolescence concerning high academic pressures and expectations, and communication difficulties (Kang, Okazaki, Abelmann, Kim-Prieto, & Shanshan, 2010). However, during emerging adulthood, the college students saw their parents differently and could appreciate more fully their parents' behaviors even though they disapproved of and resented the way they parented when they were younger.…”
Section: Future Research On Family Conflict With Chinese Immigrant Famentioning
confidence: 99%
“…From the director's descriptions as well as several brief visits, I found there is something different in the philosophy and values that this group has been pursuing from the egoism, elitism, and product-oriented learning that have commonly characterized our modern society. Such differences are also obvious when compared to the chorus I experienced in my childhood as well as to Korean culture as typically characterized by achievement and competition (Kang, Okazaki, Abelmann, Kim-Prieto, & Lan, 2010;Kim & Hong, 2007;Zhou & Kim, 2006). My experiences with music-related activities during my childhood and of the Korean community in the United States as an immigrant have shaped my inquiry on the significance of music and community engagement within Korean immigrant families, and how I, as a researcher, position myself and approach the research participants.…”
Section: Introductionmentioning
confidence: 99%